Determinants of consumer intention to go to a tourist destination. The case of - Sonia San Martín Gutiérrez; Rafael Fabricio Matos Cámara (Management Letters/Cuadernos de Gestión, 2011)
Each tourist destination has a brand the consumer can choose at the moment of travelling. This work analyzes, through a causal model empirically tested for the case of Mundo Maya-México, the paper that reputation, emotions and trust play in the consumer's intention to go to a tourist destination. A theoretical frame is developed using contributions of the signalling theory, emotions theories and relationship marketing. A face-to-face survey was carried out with consumers in travel agencies. Results confirm most of the proposed hypotheses and show interesting results: a reputation of a good management and high awareness of the tourist destination and consumer pleasure and trust in the destination reveal as antecedents of consumer intention to go to a certain tourist destination.